Language Maintenance in Labrador: Trying to hold the line - Mazurkewich, Irene (Linguistica Atlantica, 1991)
This is a work in progress on language maintenance amongst the Inuit of northern Labrador. It focuses on the bilingual development of young Inuit children who are being educated in a First Language Program; that is, they are taught in Inuttut from Kindergarten to Grade 2, at which time a switch to English as the primary language of education takes place. The preliminary results indicate that the chances of their ancestral language being maintained are in doubt. As well, there is a brief discussion of the historical decline of Inuttut from the time of contact with the first Europeans to the present. The paper outlines the complexity of the ethnic relations in this region that have evolved, and describes the growing influence of English in the native population.